O wyjaśnianiu w nauce i etyce raz jeszcze - Jedynak, Anna (Filozofia Nauki, 2005)
The paper is a reply to the polemic with my article "The Structure of Scientific Theories and Systems of Values", which presented a number of analogies between methodological and metaethical problems. These analogies can be seen if we acknowledge the information surplus of evaluative statements in comparison to normative statements (similarly in science theories are stronger than observational statements), which is indicated by the examples of actual moral questions. The basis for the polemic is the fact that its authors deny the existence of this surplus, claiming that evaluations are equivalent to and not stronger than norms. Moreover, as they reduce metaethics to the issues of meaning, and methodology to the issues of justification, they have to deny the possibility of these two domains meeting on the ground of similar problems. The paper also illustrates the reasons for a modification of meanings of certain philosophical terms that appeared in my previous article.